Ice as a kinetic and mechanistic driver of oxalate-promoted iron oxyhydroxide dissolution - Angelo P. Sebaaly; Frank van Rijn; Khalil Hanna; Jean-François Boily (Proceedings of the National Academy of Sciences, 2025)
Ice often mediates unexpected reactions in the Cryosphere, acting as a fascinating geochemical reactor. Mineral–organic interactions in frozen environments, such as soils and permafrost, are crucial for explaining the flux of soluble iron during melting events, yet the mechanisms remain misunderstood. This study elucidates the unique roles of freezing in the dissolution of iron oxyhydroxide nanoparticles (α–FeOOH) by oxalate, a low molecular weight dicarboxylate, under acidic conditions. From time-resolved experiments conducted over 4 d, we demonstrate that soluble iron was released through reactions in minute volumes of liquid water trapped between ice micrograins. Freeze concentration of nanoparticles, oxalate, and protons into this liquid water drove oxalate- and proton-promoted dissolution reactions at temperatures as low as −30 °C. Remarkably, ice at −10 °C dissolved more iron than liquid water at 4 °C under high oxalate loadings, and even more than at 25 °C under low oxalate loadings. In contrast, high salinity subdued dissolution. Also, sequential freeze-thaw cycles enhanced dissolution by releasing unreacted oxalate that was previously locked in ice. By resolving the chemical controls on mineral dissolution in ice, this work can help explain how freeze-thaw events are supplying new fluxes of soluble iron to nature.